Debating Business School Legitimacy. Attacking, Rocking, and Defending the Status Quo - Björn Rombach (Journal of Management and Business Education, 2023)
The book, 'Debating Business School Legitimacy,' is not primarily a debate book. In the introduction, the publisher apologizes for the absence of a comprehensive debate on the subject. However, the book offers a broad collection of reflections on the topic, with voices that are often more concerned than critical. Despite the apology, the book contains several contributions that undoubtedly contribute to the debate and engage the reader in a critical discussion.